Studi Kajian: Pengaruh Pelatihan dan Pengembangan Terhadap Kinerja Karyawan - M Aziz Ramadhani; Aura Belina Sabat; Natasya Priskilla Singal; Nazhira Harghea Zalianti; Mada Aditia Wardhana (Shofanah Media Berkah, 2026)
This study examines the impact of human resource training and development programs on employee performance outcomes in the context of increasingly fierce market competition. Human resources are viewed as a key asset and a driving factor for organizational success in achieving their strategic goals. Competency gaps and a lack of employee proactivity are common obstacles that reduce productivity levels. The research methodology used was quantitative, utilizing linear regression analysis to examine the relationship between variables. The results indicate that training and development, whether conducted independently or in conjunction, have a substantial and beneficial impact on employee performance. Training focuses on improving technical skills in the short term, while development aims to prepare employees for more complex challenges and roles in the future. The recommendation is the need for ongoing, open, and measurable training programs through regular evaluation to ensure the effectiveness of HR capacity building.